Incidence, risk factors, and outcomes of sclerosis in patients with chronic graft-versus-host disease - Inamoto, Yoshihiro (American Society of Hematology, 2013)
Sclerotic chronic graft-versus-host disease (GVHD) can result in disability after allogeneic hematopoietic cell transplantation. We assessed the incidence and risk factors of sclerosis and its association with transplant outcomes among 977 consecutive patients treated with systemic immunosuppression for chronic GVHD. Sclerosis was defined when cutaneous sclerosis, fasciitis, or joint contracture was first documented in the medical record. Seventy (7%) patients presented with sclerosis at the time of initial systemic treatment for chronic GVHD, and the cumulative incidence of sclerosis increased to 20% at 3 years. Factors associated with an increased risk of sclerosis included the use of a mobilized blood cell graft and a conditioning regimen with >450 cGy total body irradiation. Factors associated with a decreased risk of sclerosis included the use of an HLA-mismatched donor and a major ABO-mismatched donor. Development of sclerosis was associated with longer time to withdrawal of immunosuppressive treatment but not with risks of overall mortality, nonrelapse mortality, or recurrent malignancy. We found a substantial incidence of sclerosis in patients with chronic GVHD. Development of sclerosis can cause disability but does not affect mortality or recurrent malignancy in patients with chronic GVHD.